The (a -b)2formula is supplied to discover the square the a binomial.This (a -b)2formula is among the algebraic identities. This formula is also known as the formula because that the square the the difference of two terms. The(a -b)2formula is supplied to factorize some special species of trinomials. In this formula, wefind the square the the difference of two terms and thensolve it through the aid of algebraic identity. Let united state learn more about(a -b)2formula in addition to solved examples in the complying with section.

You are watching: A-b^2

## What Is(a-b)^2 Formula?

The (a -b)2formula is likewise widely well-known as the square of the difference in between the 2 terms. This formula is periodically used to factorizethe binomial. To find the formula of(a -b)2, we will simply multiply (a -b)(a -b).

(a -b)2=(a -b)(a -b)

= a2-ab -ba + b2

= a2-2ab + b2

Therefore,(a -b)2formula is:

(a -b)2= a2-2ab + b2

### Proof of(a − b)2Formula

Let us consider(a - b)2as the area that a square with size (a - b). In the over figure, the biggestsquare is presented with areaa2.

To prove the (a -b)2= a2-2ab + b2, consider reducing the size of all sides by element b, and it i do not care a - b. In the figure above, (a - b)2is shown by the blue area.Now subtract the vertical and horizontal strips that have the area a×b. Removed a × btwice will certainly alsoremovethe overlapping square at the bottom right cornertwice hence add b2. On rearranging the data we have(a − b)2= a2− ab − abdominal + b2. Thus this proves the algebraic identity(a − b)2= a2− 2ab + b2

Want to find complex math options within seconds?

Use our complimentary online calculator to solve difficult questions. Through brianowens.tv, uncover solutions in straightforward and easy steps.

Book a complimentary Trial Class

## Examples on(a**-**b)^2 Formula

Let usconsider couple of illustrations based onthe (a**-**b)^2 formula in this solved instances section.

**Example 1:**Find the worth of (x -2y)2by using(a -b)2formula.

**Solution:**

To find: The worth of (x - 2y)2.Let us assume that a = x and b = 2y.We will substitute these worths in (a -b)2formula:(a -b)2= a2-2ab + b2(x-2y)2= (x)2-2(x)(2y) + (2y)2= x2- 4xy + 4y2

**Answer:(x -2y)2= x2- 4xy + 4y2.**

**Example 2:**Factorize x2- 6xy + 9y2by using(a -b)2formula.

**Solution:**

To factorize: x2- 6xy + 9y2.We have the right to write the provided expression as:(x)2-2 (x) (3y) + (3y)2.Using(a -b)2formula:a2-2ab + b2=(a -b)2Substitute a = x and b = 3y in this formula:(x)2-2 (x) (3y) + (3y)2. = (x - 3y)2

**Answer:x2- 6xy + 9y2= (x - 3y)2.**

**Example 3:**Simplify the complying with using (a-b)2 formula.

(7x - 4y)2

**Solution:**

a = 7x and also b = 4yUsing formula (a - b)2 =a2 - 2ab + b2(7x)2 - 2(7x)(4y) + (4y)249x2 - 56xy + 16y2

**Answer:**(7x - 4y)2=49x2 - 56xy + 16y2.

## FAQs ~ above (a -b)^2Formula

### What Is the growth of (a -b)2Formula?

(a -b)2formula is review as a minusb entirety square. Its expansion is to express as(a - b)2 =a2 - 2ab + b2

### What Is the(a -b)2Formula in Algebra?

The (a -b)2formula is likewise known as one of the importantalgebraic identities. The is check out as a minusb entirety square. The (a -b)2formula is expressed as(a - b)2 =a2 - 2ab + b2

### How To leveling Numbers Usingthe(a -b)2Formula?

Let us know the use of the (a -b)2formula v the assist of the following example.**Example:**Find the worth of (20- 5)2using the (a -b)2formula.To find:(20- 5)2Let united state assume that a = 20 and also b = 5.We will substitute these in the formula of(a- b)2.(a - b)2 =a2 - 2ab + b2(20-5)2= 202- 2(20)(5) + 52=400-200 + 25=225**Answer:**(20-5)2= 225.

### How To use the(a -b)2Formula offer Steps?

The following steps are complied with while using(a -b)2formula.

See more: Warwick Ri Post Office Apponaug, Warwick Post Office Hours And Phone Number